Collective Identity and Protest Tactics in Yogyakarta Under The Post-Suharto Regime - DAVID EFENDI (Jurnal Studi Pemerintahan, 2015)
In response to an uncertain political situation, since 1998, Yoyakartans have engaged in resistance through groups called indigenous organizations. Such groups reproduce existing cultural resources as part of a broader movement to oppose democra-tization reforms that have been raised by the central government. Based on interviews, fieldwork and newspaper reports, this study finds that: (1) collec-tive identity can be understood in different ways from political and cultural perspectives, and indigenous groups are part of the “deep cultural resources” that establish collective identity; (2) such organizations use cultural resources in ways that conform to social movement theory; and (3) the existence of indig-enous groups contributes to shaping and reshaping the activities of the movements in which they partici-pate.